2007
DOI: 10.17221/1881-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Effects of transport distance and the season of the year on death rates among hens and roosters in transport to poultry processing plants in the Czech Republic in the period from 1997 to 2004

Abstract: ABSTRACT:Poor welfare is the cause of high mortality among hens and roosters transported to poultry processing plants. In the Czech Republic, death rates among hens and roosters in transport to poultry slaughter plants were monitored between 1997 and 2004, and their total mortality rate was in the 0.925% ± 0.479% range. Death rates among hens and roosters were influenced by the transport distance to poultry processing plants. The percentage of dead birds increased from 0.592% ± 0.575% at transport distances up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1
9

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 16 publications
(29 reference statements)
0
17
1
9
Order By: Relevance
“…High mortality has been found following transport of spent hens (Petracci et al, 2006), and this increases with transport duration. Voslarova et al (2007) found mortalities of 0.6% and 1.6% on journeys of ,50 km and up to 300 km, respectively. It has often been discussed whether these animals should be transported at all, and alternative methods of catching and killing are being sought (e.g.…”
Section: Poultrymentioning
confidence: 87%
“…High mortality has been found following transport of spent hens (Petracci et al, 2006), and this increases with transport duration. Voslarova et al (2007) found mortalities of 0.6% and 1.6% on journeys of ,50 km and up to 300 km, respectively. It has often been discussed whether these animals should be transported at all, and alternative methods of catching and killing are being sought (e.g.…”
Section: Poultrymentioning
confidence: 87%
“…In studies on broiler transportation, the main factors affecting the mortality rate and live weight loss during transportation between the farms and the processing plants are catching method (Ekstrand, 1998;Knierim & Gokce, 2003), transportation distance (Nijdam et al, 2004;Vecerek et al, 2006;Voslarova et al, 2007;Ondrasovicova et al, 2008;Sowinska et al, 2013), time of transportation (Bayliss & Hinton, 1990;Warriss et al, 1992;Nijdam et al, 2004;Bianchi et al, 2005;Luptakova et al, 2012), lairage time at the reception area (Bayliss & Hinton, 1990;Nijdamet al, 2004, Vieira et al, 2010, transportation duration (Bayliss & Hinton, 1990), crate stocking density (Bayliss & Hinton, 1990;Chauvin et al, 2011), seasonal conditions (Vecerek et al, 2006;Petracci et al, 2006;Voslarova et al, 2007;Drain et al, 2007;Elsayed, 2014), daily average temperature (Warriss et al, 2005;Elsayed, 2014), and weather conditions (Chauvin et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Environmental factors, including temperature and humidity (Warriss et al, 2005; Chauvin et al, 2011), season and time of the day (Moran & Bilgili, 1995;Petracci et al, 2006;Vecerek et al, 2006;Drain et al, 2007;Voslarova et al, 2007;Elsayed, 2014), distance between the poultry farm and the processing plant (Nijdamet al, 2004;Voslarova et al, 2007;Ondrasovicova et al, 2008;Sowinska et al, 2013;Vecerek et al, 2016), and transportation time (Bayliss & Hinton, 1990;Warriss et al,1992;Nijdam et al, 2004;Bianchi et al, 2005) also influence production losses.…”
Section: Introductionmentioning
confidence: 99%
“…Por isto, em diversos estudos têm sido observado que quanto maior a distância de transporte, maior foi o número de aves mortas na chegada ao abatedouro (Barbosa Filho et al, 2009). Voslarova et al (2007) encontraram resultados de mortalidade elevados em distâncias acima de 100 km, sendo que a menor proporção de aves mortas encontrada (0,6%) foi registrada em distâncias abaixo de 50 km. Seja nos meses mais quentes ou frios, o período da tarde é o mais problemático para o transporte, com relação ao estresse térmico das aves (Barbosa Filho et al, 2009).…”
Section: Efeito Do Estresse Na Qualidade Da Carne De Avesunclassified